Borderline personality disorder in an intermediate psychological therapies service. Issue 3 (27th May 2017) - Ryan, Seamus; Danquah, Adam N.; Berry, Katherine; Hopper, Mary
ABSTRACT: The intermediate psychological therapies service is provided for individuals referred with common mental health problems within the primary care psychological therapies service, but whose difficulties are longstanding and/or complex. The prevalence of borderline personality disorder (BPD) in intermediate psychological therapy services has not been researched to-date. The current study aimed to measure the prevalence of BPD amongst patients attending intermediate psychological therapies ( n  = 63). The prevalence of BPD was established by identifying the number of patients who met DSM-IV criteria. BPD prevalence amongst patients attending an intermediate psychological therapy service was 37%. The high proportion of patients presenting with BPD indicates the potential need for staff training and supervision in how to manage such high levels of need at this service level. This is the first study to report prevalence rates of BPD specifically in an intermediate care psychological therapy service.